INOVASI KLEPON LABU KUNING DENGAN SUBTITUSI TEPUNG UBI PORANG SEBAGAI ALTERNATIF KUE TRADISIONAL - Rizal Dwi Setyawan; Ita Fatkhur Romadhoni; Ila Huda Puspita Dewi; Mafisa Restami (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Klepon is a traditional snack made from glutinous rice flour with limited nutritional content. This study aims to analyze the effect of porang flour substitution and pumpkin addition on the organoleptik quality of klepon and to determine the best formulation. The study used an experimental method with a single-factor Completely Randomized Design (CRD) with a single factor was employed, conducted in two experimental stages: varying the substitution of porang flour and varying the addition of pumpkin, performed separately. A hedonic test on a 1 to 5 scale was conducted on six formulations by 30 panelists (5 trained and 25 semi-trained panelists), covering the attributes of color, aroma, taste, texture, and overall liking. Data were analyzed using one-way ANOVA followed by Duncan's test. The results showed that porang flour substitution and pumpkin addition had a significant effect (p < 0.05) on all organoleptik attributes. Increasing porang flour substitution reduced the texture chewiness and product acceptance, while pumpkin addition improved color brightness, aroma, and taste. The best formulation was obtained in sample 542 (20 g porang flour substitution and 40 g pumpkin) with the highest overall liking score (4.33) and the best texture (4.30). This formulation has the potential to be developed as an innovative local-based klepon product.